Digital Ethics for Teens: Building Social Awareness in Using the Internet and AI - Sopi Sapriadi; Aldo Eko Syaputra; Kiki Hariani Manurung; Nova Hayati; Wulandari (Universitas Putra Indonesia YPTK Padang, 2026)
This Community Service Program aimed to enhance critical digital literacy and ethical awareness regarding the use of the internet and Artificial Intelligence (AI) among teenagers at SMA Negeri 1 Lembah Gumanti through an educational initiative titled “Digital Ethics for Teens.” The activity began with a situational analysis that revealed a high level of gadget and social media use among students, which was not matched by an adequate understanding of digital ethics, algorithmic risks, and personal data security. The intervention was implemented through a 50-minute interactive session that combined participatory lectures, simulations of violations of the Electronic Information and Transactions Law, and discussions on the social impact of AI, cyberbullying, plagiarism, hoaxes, and filter bubble phenomena. Evaluation using a before-after assessment approach indicated a significant improvement in students’ ability to identify ethical and unethical behavior, manage privacy, and understand the legal and social consequences of their digital activities. The main outputs included a draft article for a nationally accredited SINTA journal, educational modules and presentation media, and the establishment of a digital ethics youth community serving as peer educators at the school. For sustainability, a micro-curriculum on Digital Citizenship and AI Awareness was planned to be integrated into ICT subjects and developed into open modules for other schools with similar characteristics.